Comparative study of innovative blends prepared by fortification of date powder to alleviate child malnutrition. Issue 11 (12th October 2020) - Raza, Nighat; Arshad, Muhammad Umair; Saeed, Farhan; Farooq, Umar; Naz, Ambreen; Murtaza, Mian Shamas; Badar Ul Ain, Huma; Tufail, Tabussam; Imran, Muhammad; Anjum, Faqir Muhammad
Abstract: Child malnutrition is one of the biggest problems in developing countries with higher level of food insecurity. Pakistan is 5th largest producer of date fruit; therefore, its processing and products should be explored in various dimensions. Being rich source of minerals and sugars, it can contribute in weaning foods in a good manner. In current study, three blends were prepared with specific proportions of spray‐dried date powder and rich in specific proportions. They were compared with each other and control (free of date powder). The nutritional profile of the formulations revealed that 100 g of each formulation included all macronutrients in compliance with the requirements of Food and Agriculture Organization for weaning formulations; moreover, they are enriched with minerals due to presence of date powder. The iron contents reached up to 12.74 ± 0.16 mg/100 g. The phosphorus, zinc, and potassium contents also increased with the increase in date powder subsequently. Physicochemical properties exhibited in compliance with the requirement of the weaning foods. The protein quality was assessed both in vivo and in vitro. Amino acid profiling indicated that the limiting amino acid in F1 and control were lysine but in F2 and F3 were threonine. This is suggested that date powder might contain good quality protein that was further explained in biological studies, the formulations that contained higher amount of date powder reveled better PDCAAS score 86.76 ± 4.5, true digestibility 84 ± 4.36, biological value 69.45 ± 0.69, net protein utilization 73.82 ± 1.46, and protein efficiency score 1.18 ± 0.07. The sensory evaluation revealed that F2 showed better result in overall acceptability. Thus, date powder is suggested to be used as good constituent that can fortify mineral contents and sugar contents of the weaning foods. Abstract : The amelioration of weaning food to uplift child health required novel approaches. The effort made in current study showed good results regarding weaning blends. Date powder contributed to protein contents, improve the micromineral and amino acid profile of the blends clearly, and the control with no date powder was lacking good protein quality, good amino acid score, and mineral contents. Therefore, date powder blending for weaning mixes preparation was proved in current study.